Overexpression of FTO inhibits excessive proliferation and promotes the apoptosis of human glomerular mesangial cells by alleviating FOXO6 m6A modification via YTHDF3-dependent mechanisms - Zhuang, Xingxing; Liu, Tao; Wei, Liangbing; Gao, Jiarong (Frontiers in Pharmacology, 2023)
Background: N6-methyladenosine (m6A) is a prevalent post-transcriptional modification presented in messenger RNA (mRNA) of eukaryotic organisms. Chronic glomerulonephritis (CGN) is characterised by excessive proliferation and insufficient apoptosis of human glomerular mesangial cells (HGMCs) but its underlying pathogenesis remains undefined. Moreover, the role of m6A in CGN is poorly understood. Methods: The total level of m6A modification was detected using the m6A quantification assay (Colorimetric). Cell proliferation was assessed by EdU cell proliferation assay, and cell apoptosis was detected by flow cytometry. RNA sequencing was performed to screen the downstream target of fat mass and obesity-associated protein (FTO). MeRIP-qPCR was conducted to detect the m6A level of forkhead box o6 (FOXO6) in HGMCs. RIP assay was utilized to indicate the targeting relationship between YTH domain family 3 (YTHDF3) and FOXO6. Actinomycin D assay was used to investigate the stability of FOXO6 in HGMCs. Results: The study found that the expression of FTO was significantly reduced in lipopolysaccharide (LPS)-induced HGMCs and renal biopsy samples of patients with CGN. Moreover, FTO overexpression and knockdown could regulate the proliferation and apoptosis of HGMCs. Furthermore, RNA sequencing and cellular experiments revealed FOXO6 as a downstream target of FTO in regulating the proliferation and apoptosis of HGMCs. Mechanistically, FTO overexpression decreases the level of FOXO6 m6A modification and reduces the stability of FOXO6 mRNA in a YTHDF3-dependent manner. Additionally, the decreased expression of FOXO6 inhibits the PI3K/AKT signaling pathway, thereby inhibiting the proliferation and promoting apoptosis of HGMCs. Conclusion: This study offers insights into the mechanism through which FTO regulates the proliferation and apoptosis of HGMCs by mediating m6A modification of FOXO6 mRNA. These findings also suggest FTO as a potential diagnostic marker and therapeutic target for CGN.